Schwann cell TRPA1 mediates neuroinflammation that sustains macrophage-dependent neuropathic pain in mice. Issue 1 (December 2017) - De Logu, Francesco; Nassini, Romina; Materazzi, Serena; Carvalho Gonçalves, Muryel; Nosi, Daniele; Rossi Degl'Innocenti, Duccio; Marone, Ilaria; Ferreira, Juliano; Li Puma, Simone; Benemei, Silvia; Trevisan, Gabriela; Souza Monteiro de Araújo, Daniel; et al.
Abstract It is known that transient receptor potential ankyrin 1 (TRPA1) channels, expressed by nociceptors, contribute to neuropathic pain. Here we show that TRPA1 is also expressed in Schwann cells. We found that in mice with partial sciatic nerve ligation, TRPA1 silencing in nociceptors attenuated mechanical allodynia, without affecting macrophage infiltration and oxidative stress, whereas TRPA1 silencing in Schwann cells reduced both allodynia and neuroinflammation. Activation of Schwann cell TRPA1 evoked NADPH oxidase 1 (NOX1)-dependent H2 O2 release, and silencing or blocking Schwann cell NOX1 attenuated nerve injury-induced macrophage infiltration, oxidative stress and allodynia. Furthermore, the NOX2-dependent oxidative burst, produced by macrophages recruited to the perineural space activated the TRPA1–NOX1 pathway in Schwann cells, but not TRPA1 in nociceptors. Schwann cell TRPA1 generates a spatially constrained gradient of oxidative stress, which maintains macrophage infiltration to the injured nerve, and sends paracrine signals to activate TRPA1 of ensheathed nociceptors to sustain mechanical allodynia. Following peripheral nerve injury, influx of immune cells to the site may contribute to the development of chronic pain. Here the authors show that TRPA1 is expressed on Schwann cells and contributes to immune cell influx in a mouse model of neuropathic pain.